2008
DOI: 10.1007/s11431-008-0162-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of lateral growth on the structural properties of high temperature GaN layer

Abstract: The role of lateral growth on the structural properties of high temperature (HT) GaN epitaxial layer has been investigated by means of transmission electron microscopy (TEM) and X-ray diffraction (XRD). Variations of the lateral growth rate of HT GaN in metal-organic chemical vapor deposition (MOCVD)can be obtained by changing the V/III ratio. It is found that under higher lateral growth rate, dislocation is easier to bend into subgrains away from c axis, and the position where bend occurs is closer to the buf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The results showed that the XRC-FWHM value of the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) plane along the c-axis direction and m-axis direction increased with increasing SiH 4 flow rate, which demonstrated that the crystalline quality along the c-axis direction slightly decreased. It means that the dislocation density increases with increasing SiH 4 flow rate.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…The results showed that the XRC-FWHM value of the (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) plane along the c-axis direction and m-axis direction increased with increasing SiH 4 flow rate, which demonstrated that the crystalline quality along the c-axis direction slightly decreased. It means that the dislocation density increases with increasing SiH 4 flow rate.…”
Section: Resultsmentioning
confidence: 96%
“…The peak shape analyses of XRD were based on the separation of the Gaussian and Lorentzian broadening using Pseudo-Voigt function [13,14].…”
Section: Yl Bands So the Yl Could Be Enhanced By The Transitions Betmentioning
confidence: 99%
See 2 more Smart Citations